New route for 1-substituted hydantoins - Orazi, Orfeo Osvaldo (1965)
Alkytation reactions on hydantoins (I) lead smoothly to 3-alkyl derivatives; more rigorous conditions allow further substitution at position 1 provided the N1-H group is activated by an aryl group or an ethylenic bond attached to the adjacent C52,a. All the hitherto available methods for the not readily accessible 3-unsubstituted-1-alkylhydantoins (IV) require placing the substituent at the appropriate nitrogen atom prior to the complete formation of the hydantoin system.